Moderasi Beragama: Wujud Cinta Tanah Air Melalui Pemahaman Nilai-Nilai Pancasila - Afdhal Musyra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research explores the interconnection between religious moderation and the values of Pancasila as an expression of patriotism in the context of Indonesia. Through a qualitative approach combining literature analysis and theoretical review, this study identifies that religious moderation substantially aligns with the principles of Pancasila, emphasizing unity, social justice, democracy, and civilized humanity. These findings highlight the pivotal role of Pancasila values in shaping a pluralistic and inclusive national identity, as well as in promoting interreligious harmony in Indonesia. The discussion underscores the importance of enhancing religious education oriented towards moderation, strengthening the role of religious institutions in promoting dialogue and tolerance, and encouraging community participation in fostering harmony. The proposed recommendations include expanding proven-effective religious moderation programs and allocating adequate resources to support the practical implementation of Pancasila values in everyday community life. This research aims to provide guidance for policymakers, academics, and practitioners to strengthen the foundation of interreligious harmony and advance Pancasila values as the moral and ethical cornerstone of the Indonesian nation.